Teaming with Teams! Making it work for your Language Classroom - Athanasiou, Androulla (My University, 2026)
A 90 minute training session on using OneNote, Breakout Rooms and Forms in English Language Teaching. The workshop was offered to the Pancyprian Association of English Language Teachers (PAET)